Dampak Pandemi Covid-19 Terhadap Pola Perilaku Sehat: Analisis Kebiasaan Baru Yang Disesuaikan Di Kalangan Masyarakat - Ambia Nurdin; khairuman; diana; Dian Rahayi (Public Health Journal, 2024)
This article analyzes the influence of the COVID-19 pandemic on the patterns of healthy behavior among communities, focusing on the newly adapted habits to sustain amidst the pandemic. Data sources are drawn from computerized databases such as PubMed, ScienceDirect, Elsevier, Portal Garuda, and Google Scholar, with inclusion criteria for relevant research articles published between 2019-2023, available in Indonesian or English, and open access. Five articles meeting the inclusion criteria were then analyzed, and data synthesis was conducted. The research findings indicate the emergence of new habits related to healthy lifestyles adapted by communities following the onset of the COVID-19 pandemic. This demonstrates that the COVID-19 pandemic has brought about significant changes in community behavior patterns, particularly in efforts to maintain health and resilience amidst the threatening pandemic situation.